Mental health service provision in low and middle-income countries: recent developments. Issue 4 (July 2016) - Weinmann, Stefan; Koesters, Markus
Abstract : Purpose of review: The study discusses key issues and concepts of how to provide basic mental health services for people with mental disorders in low and middle-income countries (LAMICs). Recent findings: In the last years a considerable gap between mental healthcare needs and available services in LAMICs has been documented. The transformation of hospital-based to community-based mental health and the building of accessible services in low-resource settings require mental health training of primary care providers, task-sharing/task-shifting models, involvement of families and peers and basic models of community rehabilitation. Several international initiatives have been set up to increase the evidence base and test the feasibility, acceptability, and effectiveness of these approaches which are not new but which have been implemented in only a small amount of LAMICs. A combination of interventions on different levels (governance, legislation, providers, and community) is necessary. Summary: It remains to be shown how the recent global mental health movement, beyond increasing international financial resources, will be helpful in finding locally and culturally sensitive solutions to reduce the mental health gap in LAMICs. Although concepts of a well designed mix of services are available, solutions to reduce implementation barriers must be local, and implementation strategies may vary considerably and still lack a sufficient evidence base.